The Challenge of Fostering Healthy Organizations: An Empirical Study on the Role of Workplace Relational Civility in Acceptance of Change and Well-Being - Di Fabio, Annamaria; Giannini, Marco; Loscalzo, Yura; Palazzeschi, Letizia; Bucci, Ornella; Guazzini, Andrea; Gori, Alessio (Frontiers in Psychology, 2016)
The world of work in the 21st century is characterized by globalization, instability, and unavoidable change. Organizations need to develop a positive relational environment in the workplace thereby enabling workers to enhance their personal resources in order to face with ongoing changes in the sphere of work for promoting their well-being. Against this background, the aim of this research was to examine the relationship between workplace relational civility and both acceptance of change and well-being (hedonic well-being as well as eudaimonic well-being) beyond the effect of personality traits. The following instruments were administered to 261 Italian workers: the Ten Item Personality Inventory (TIPI), the Acceptance of Change Scale (ACS), the Satisfaction With Life Scale (SWLS), and the Meaningful Life Measure (MLM). The results of hierarchical regression analyses revealed that workplace relational civility explained a percentage of incremental variance beyond personality traits in relation to acceptance of change, life satisfaction, and meaning in life. These results underscore the positive relationship between workplace relational civility and acceptance of change, hedonic well-being, and eudaimonic well-being, offering new research and intervention opportunities to meet the challenge of fostering healthy organizations.